In situ gas fuel production during the treatment of textile wastewater at supercritical conditions - Kipcak, Ekin; Akgun, Mesut (IWA PUBLISHING, 2013)
Supercritical water gasification has recently received much attention as a potential alternative to energy conversion methods applied to aqueous/non-aqueous biomass sources, industrial wastes or fossil fuels such as coal because of the unique physical properties of water above its critical conditions (i.e. 374.8 degrees C and 22.1 MPa). This paper presents the results obtained for the hydrothermal gasification of textile wastewater at supercritical conditions. The experiments were carried out at five reaction temperatures (between 450 and 650 degrees C) and five reaction times (between 30 and 150 s), under a constant pressure of 25 MPa. It was found that the gaseous products contained considerable amounts of hydrogen, carbon monoxide, carbon dioxide, and C-1-C-4 hydrocarbons, such as methane, ethane, propane and propylene. The maximum amount of the obtained gaseous product was 1.23 mL per mL textile wastewater, at a reaction temperature of 600 degrees C, with a reaction time of 150 s. At this state, the product comprised 13.02% hydrogen, 38.93% methane, 4.33% ethane, 0.10% propane, 0.01% propylene, 7.97% carbon monoxide, 27.22% carbon dioxide and 8.00% nitrogen. In addition, a 62.88% decrease in the total organic carbon (TOC) content was observed and the color of the wastewater was removed. Moreover, for the hydrothermal decomposition of the textile wastewater, a first-order reaction rate was designated with an activation energy of 50.42 (+/- 2.33) kJ/mol and a pre-exponential factor of 13.29 (+/- 0.41) s(-1).
Keywords: gas fuels; hydrothermal gasification; supercritical water; textile wastewater; HYDROGEN-PRODUCTION; BIOMASS GASIFICATION; OXIDATION; GLUCOSE; CELLULOSE; REACTOR; CATALYSTS; COMPOUND; KINETICS; Engineering; Environmental Sciences & Ecology; Water Resources